How socioeconomic inequalities impact pathways of care for coronary artery disease among elderly patients: study protocol for a qualitative longitudinal study. Issue 11 (9th November 2015) - Schröder, Sara L; Fink, Astrid; Schumann, Nadine; Moor, Irene; Plehn, Alexander; Richter, Matthias
Abstract : Introduction: Several studies have identified that socioeconomic inequalities in coronary artery disease (CAD) morbidity and mortality lead to a disadvantage in patients with low socioeconomic status (SES). International studies have shown that socioeconomic inequalities also exist in terms of access, utilisation and quality of cardiac care. The aim of this qualitative study is to provide information on the impact of socioeconomic inequalities on the pathway of care for CAD, and to establish which factors lead to socioeconomic inequality of care to form and expand existing scientific theories. Methods and analysis: A longitudinal qualitative study with 48 patients with CAD, aged 60–80 years, is being conducted. Patients have been recruited consecutively at the University Hospital in Halle/Saale, Germany, and will be followed for a period of 6 months. Patients are interviewed two times face-to-face using semistructured interviews. Data are transcribed and analysed based on grounded theory. Ethics and dissemination: Only participants who have been informed and who have signed a declaration of consent have been included in the study. The study complies rigorously with data protection legislation. Approval of the Ethical Review Committee at the Martin-Luther University Halle-Wittenberg, Germany was obtained. The results of the study will be presented at several congresses, and will be published in high-quality peer-reviewed international journals. Trial registration number: This study has been registered with the German Clinical Trials Register and assigned DRKS00007839.